Ecoregional Variation of Crimean Pine (Pinus nigrasubspeciespallasiana[Lamb.] Holmboe) Stand Growth - Seki, Mehmet; Sakici, Oytun Emre (Springer Science and Business Media LLC, 2022)
AbstractInvestigation and numerical determination of the effects of ecologically different regions on forest growth are important issues to be considered for sustainable forest management. In this study, differences in growth patterns of Crimean pine (Pinus nigra subsp. pallasiana [Lamb.] Holmboe) stands among the ecoregions located in the Kastamonu region of northwestern Turkey were investigated. For this purpose, stand-level growth models for dominant height, number of trees, basal area, and volume were fitted using the data from 274 sample plots and 293 stem analysis in even-aged, pure, and productive Crimean pine stands. The nonlinear extra sum of squares method and graphical examinations revealed that growth characteristics of these Crimean pine stands were affected by ecoregional differences. Ecoregion-based growth models, which are more flexible and have the ability to reflect the ecoregional differences in growth patterns, were found to be superior to regional models. Applying general models without any ecoregional classification resulted in biases of 5.3%, 23.1%, 5.5%, and 6.2% in the estimates of dominant height, number of trees, basal area, and volume of Crimean pine stands, respectively. The results showed that ecological differences must be considered in studies on forest growth modeling and forest management.
Keywords: 15. Life on land